A Ca(2+)/Calmodulin-Dependent Protein Kinase ModulatesDrosophila Photoreceptor K(+) Currents: A Role in Shaping the Photoreceptor Potential - Peretz, Asher (J Neurosci, 1998)
Light activation of Drosophila photoreceptors leads to the generation of a depolarizing receptor potential via opening of transient receptor potential and transient receptor potential-like cationic channels. Counteracting the light-activated depolarizing current are two voltage-gated K(+) conductances, I(A) andI(K), that are expressed in these sensory neurons. Here we show that Drosophilaphotoreceptors I(A) andI(K) are regulated by calcium–calmodulin (Ca(2+)/calmodulin) via a Ca(2+)/calmodulin-dependent protein kinase (CaM kinase), with I(K) being far more sensitive than I(A). Inhibition of Ca(2+)/calmodulin by N-(6 aminohexyl)-5-chloro-1-naphthalenesulfonamide or trifluoperazine markedly reduced the K(+) current amplitudes. Likewise, inhibition of CaM kinases by KN-93 potently depressedI(K) and accelerated its C-type inactivation kinetics. The effect of KN-93 was specific because its structurally related but functionally inactive analog KN-92 was totally ineffective. In Drosophila photoreceptor mutantSh(KS133), which allows isolation ofI(K), we demonstrate by current-clamp recording that inhibition of I(K) by quinidine or tetraethylammonium increased the amplitude of the photoreceptor potential, depressed light adaptation, and slowed down the termination of the light response. Similar results were obtained when CaM kinases were blocked by KN-93. These findings place photoreceptor K(+) channels as an additional target for Ca(2+)/calmodulin and suggest thatI(K) is well suited to act in concert with other components of the signaling machinery to sharpen light response termination and fine tune photoreceptor sensitivity during light adaptation.